2015
DOI: 10.1007/s12298-015-0321-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving key enzyme activities and quality of rice under various methods of zinc application

Abstract: Zinc (Zn) is an important micronutrient for the physiology of plants. It is poorly available to the plants in soil solution. A pot experiment was conducted to evaluate effectiveness of various Zn application methods on key enzyme activities and protein content of two contrasting rice genotypes viz., PD16 (Zn efficient) and NDR359 (Zn inefficient). The treatments were, control (0 mg Zn kg Among all the methods tested soil+foliar application of Zn fertilizers was found most effective in increasing superoxide dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…It was reported that a Zn efficient rice variety contains higher chlorophyll content than a Zn inefficient rice variety under Zn application [26]. According to the current results, two Se rich rice genotypes, Z3055B and Z5097B contained the higher total chlorophyll content.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…It was reported that a Zn efficient rice variety contains higher chlorophyll content than a Zn inefficient rice variety under Zn application [26]. According to the current results, two Se rich rice genotypes, Z3055B and Z5097B contained the higher total chlorophyll content.…”
Section: Discussionsupporting
confidence: 51%
“…It has been reported that Zn promotes chlorophyll synthesis as a structural and catalytic component of proteins, enzymes, and as co-factor for normal development of pigment biosynthesis [25]. In previous reports, 5 mg/kg of soil Zn application increased total chlorophyll content in rice leaves and 14 Zn mg/kg of soil could increase SPAD values improving plant photosynthetic characteristics under water stress in wheat [26,27].…”
Section: Discussionmentioning
confidence: 95%
“…Both microelements also are necessary in activation of many enzymes that existent in photosynthetic tissues and necessary for chlorophyll formation (Ramani & Kannan 1985). It was reported that zinc play a vital role in activation of enzymes related to protein biosynthesis and metabolism of carbohydrates (Mathpal et al 2015). In the current study, our results showed foliar application of ZnO and FeO GNPs plus chicken manure caused a significant improvement in growth parameters (Table 3), as Chaudhuri & Malodia (2017) reported.…”
Section: Discussionmentioning
confidence: 99%
“…K also has its importance in parallel to other macronutrients that contribute in various biochemical and physiological functions ( Hasanuzzaman et al, 2018 ; Liljeroth et al, 2016 ) Like macronutrients, the micronutrients have also been reported to enhance the plant disease resistance by reducing disease severity. In plant metabolism, a key role is played by zinc (Zn) contributes in various reaction as enzyme co-factor like energy transfer, redox reactions, and stabilization of ribosomal fractions for protein synthesis ( Mathpal et al, 2015 ; Noulas et al, 2018 ). Numerous researches suggested that the proper application of Zn enhances the growth and productivity in a diverse range of crops including beans, chickpea, maize, rice, cotton and wheat ( Khan et al, 2018 ; Khattak et al, 2016 ; Rehman et al, 2018 ).…”
mentioning
confidence: 99%